Customer Satisfaction with the Quality of Retail Service During the Covid-19 Pandemic in the Kingdom of Saudi Arabia - Al-Wahashi, Abdulwahab (The Arab Journal of Administration, 2023)
This study aims to explore customer satisfaction with the quality of traditional and electronic retail service, which is represented in several dimensions (reliability, responsiveness, flexibility, accessibility, empathy, and security), in light of an exceptional and relatively different situation (the corona pandemic covid-19) Using the descriptive analytical approach, the questionnaire was designed to include all components and formulations of the study model. The study community consists of individual clients in the Kingdom of Saudi Arabia. The study used the electronic questionnaire to collect data from the participants. The questionnaires were sent to the target group in all regions of the Kingdom of Saudi Arabia with a number of A total and capacity of 430 clients, where (402) usable responses were received from the total number sent with a return rate of (93%), and the (SPSS) program was used to analyze the data and obtain the results. The results showed a significant effect of retail service quality (reliability, responsiveness, flexibility, accessibility, empathy, safety) on customer satisfaction during the covid-19 pandemic, and the results also showed that there were no statistically significant differences for the differences between customer satisfaction during the COVID-19 pandemic. Corona covid-19 pandemic according to the following demographic variables (gender, educational qualification, monthly income, employment status, geographical area), while the results showed statistical differences with significant significance for the differences between customer satisfaction during the corona covid-19 pandemic according to the variable (age).